Curve Graphs and Garside Groups - Calvez, M (Springer Netherlands, 2017)
We present a simple construction which associates to every Garside group a metric space, called the additional length graph, on which the group acts. These spaces share important features with curve graphs: they are δ-hyperbolic, infinite, and typically locally infinite graphs. We conjecture that, apart from obvious counterexamples, additional length graphs have always infinite diameter. We prove this conjecture for the classical example of braid groups (Bn,Bn+,Δ); moreover, in this framework, reducible and periodic braids act elliptically, and at least some pseudo-Anosov braids act loxodromically. We conjecture that for Bn, the additional length graph is actually quasi-isometric to the curve graph of the n times punctured disk. © 2016, Springer Science+Business Media Dordrecht.